Topology optimization of laminated composite structures under harmonic force excitations. (February 2022) - Hu, Zheng; Sun, Shiping; Vambol, Oleksii; Tan, Kun
In this paper, a topology optimization approach for the design of laminated composite structures under harmonic force excitations is proposed. A novel method is developed to calculate the harmonic response for composite laminates, which consists of two steps: firstly, based on the strain energy approach, the damping matrix model of composite laminates is established with the proportional damping assumption; then, the displacement response is calculated by the mode acceleration method The design objective of topology optimization is to minimize the displacement amplitude at the concerning point with an excitation frequency or a frequency band. An extended polynomial interpolation scheme is introduced to penalize the stiffness, damped stiffness and mass of elements. The analytical sensitivities of the objective and constraint functions to the density variables are derived in detail, and the globally convergent method of moving asymptotes is used to solve the optimization problem. Numerical examples are performed to demonstrate the effectiveness and feasibility of the proposed topology optimization method in improving the dynamic performance of laminated composite structures. The influence rules of excitation frequency and layer sequence on topologic shape are also discussed.